Global diversity of soil-transmitted helminths reveals population-biased genetic variation that impacts diagnostic targets - Marina Papaiakovou; Andrea Waeschenbach; Olumide Ajibola; Sitara SR Ajjampur; Roy M. Anderson; Robin Bailey; Jade Benjamin-Chung; Maria Cambra-Pellejà; Nicolas R. Caro; David Chaima; Rubén O. Cimino; Piet Cools; et al. (Nature Communications)
Abstract Soil-transmitted helminths (STHs) are intestinal parasites that affect over a billion people worldwide. STH control relies on microscopy-based diagnostics to monitor parasite prevalence and enable post-treatment surveillance; however, molecular diagnostics are rapidly being developed due to increased sensitivity, particularly in low-STH-prevalence settings. The genetic diversity of helminths and its potential impact on molecular diagnostics remain unclear. Using low-coverage genome sequencing, we assess the genetics of STHs within worm, faecal, and purified egg samples from 27 countries, identifying differences in the genetic connectivity and diversity of STH-positive samples across regions and cryptic diversity between closely related human- and pig-infective species. We define substantial copy number and sequence variants in current diagnostic target regions and validate the impact of genetic variation on qPCR diagnostics using in vitro assays. Our study provides insights into the diversity and genomic epidemiology of STHs, highlighting both the challenges and opportunities for developing molecular diagnostics needed to support STH control efforts.